Initial Data on Clinical Use of Generic Romiplostim for Second-Line and Subsequent Therapy of Immune Thrombocytopenia in India - Suvir Singh; Komalpreet Kaur (Indian Journal of Medical Specialities)
Introduction: Over 50% of adults with immune thrombocytopenia (ITP) require second-line therapy after steroids, but these options are plagued by low rates of response, which are often delayed by 2–3 months. Romiplostim is a thrombopoietin receptor agonist (TPO-RA) that has shown significant efficacy in this setting and is now available in a generic formulation. No data on the efficacy and safety of the same are available in the India context. Methodology: This study was conducted from August 2019 to July 2020. Romiplostim was used for patients with ITP that was (a) steroid or intravenous immunoglobulin (IvIg) refractory or (b) not responding to other second-line agents. Results: A total of 11 patients were included in the analysis (M:F = 6:5) with a median age of 44 years (range, 18–67). Initial therapy was corticosteroids for all patients of which nine (81%) had an initial response. Second-line therapy included azathioprine for six patients (54%) and IvIg for four (36%) patients. All patients were refractory to the second-line therapy and initiated on romiplostim at a median dose of 3.68 μg/kg/week (range, 2.7–6.2). A sustained response was observed in 10 patients (90.9%) after a median duration of 13 days (range, 2–32). At a median follow-up of 5.5 months, nine patients (81%) had stable platelet counts. Conclusion: Initial data suggest that generic romiplostim is an effective and safe second-line medication for ITP and can potentially avoid splenectomy in steroid and IvIg refractory patients. Prospective follow-up of more patients will provide a better perspective on efficacy and cost-effectiveness of TPO-RAs.